Investigations on the Occurrence of Silica in Indian Timbers - Sharma, Manju; Ramesh Rao, K. (Indian Forester, 1970)
Silica content of 134 species of wood belonging to 80 genera and 35 families has been investigated both anatomically and gravimetrically. It has been found to be absent in 66 species. In the remaining 68 species, the silica content varies from 0.05 per cent in Cleistanthus collinus Benth. to over 7 per cent in Elaeocarpus lanceaefolius Roxb. Silica occurs in the form of inclusions in 54 species and as vitreous silica in 13 species. One species Gironniera reticulata Thw. has both the types. Silica inclusions are very commonly found in ray cells, and also to some extent in vertical parenchyma but only rarely in fibres. The inclusions are extremely variable in shape and size. Vitreous silica, unlike inclusions occurs mostly in vessels, sometimes also in parenchyma and fibres. The importance of silica in timber identification and utilization and its significance in taxonomy are also discussed.